From crisis to opportunity: enhancing anatomy education in a post-COVID world: the Universiti Sains Malaysia experience - Sofiah Hanis Ahmad Hisham; Siti Nurma Hanim Hadie; Fazlina Kasim; Shamsi Amalina Shamsuddin (Korean Journal of Medical Education)
The coronavirus disease 2019 pandemic has fundamentally reshaped anatomy education, offering invaluable insights to guide the future of anatomy pedagogy. As we transition into a post-pandemic era, it is crucial to integrate the lessons learned to create a more resilient, flexible, and effective educational environment. This paper examines the transformative strategies implemented at Universiti Sains Malaysia during the pandemic, focusing on the empowerment of blended learning, technology-enhanced tools, student-centered learning practical sessions, and enhancement of formative assessment. These strategies include integrating digital learning resources, such as the Virtual Anatomy Museum and online histology quizzes, with in-person instruction, fostering a supportive and interactive learning environment. Additionally, practical sessions were redesigned to emphasize collaborative learning, peer teaching, and developing critical thinking and communication skills. Formative assessments were integrated to provide continuous feedback and support ongoing learning. This comprehensive approach not only enhanced students’ understanding of anatomical concepts but also improved their emotional well-being and overall learning experience. The lessons learned from the pandemic have paved the way for a more innovative and adaptive anatomy education that is well-prepared for future challenges.